Six Steps towards an Object-oriented Social Theory (O.O.S.T) - Pinho, Thiago (Conatus - Journal of Philosophy, 2023)
In the approach that sustains this entire essay, besides my own trajectory as a researcher, the path moves away from the orthodox tradition, the more Kantian one, incorporating in Social Theory a philosophical line for a long time forgotten, by including figures such as Baruch Spinoza (1632-1677), the founding father, Friedrich Nietzsche (1844-1900), Alfred North Whitehead (1861-1947), Henri Bergson (1859-1941), Gilbert Simondon (1924-1989), Gilles Deleuze (1925-1995) and many others. They would be the famous authors of vitalism, also known as philosophers of life (Lebensphilosophie), philosophers of process, or philosophers of affect. What are the implications when these figures invade the field of Social Theory, which characteristics can be found and, mainly, which advantages when compared with their more orthodox side and their insistent commitment to Kantian philosophy and its transcendental by-products (power, culture, ideology, discourse, etc)? Following this and other questions, six points will be considered as representative of what we call here an Object-Oriented Social Theory (O.O.S.T.).